Analisis Kualitas Layanan Website dengan menggunakan Metode Webqual 4.0 dan Importance and Performance Analysis (IPA) pada UPT Perpustakaan Proklamator Bung Karno - Harry Bali Kusuma; Suprapto Suprapto; Hanifah Muslimah Az-Zahra (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
The development of information and communication technology has an important meaning in building the quality of library services. The website is an information media and electronic-based promotion that is expected as an effort to provide services at the Bung Karno Proclamator Library UPT. The presence of this study is to measure the quality of website services using the webqual 4.0 instrument based on 3 dimensions (usability, information quality, and service interaction quality), then analyzed using Importance Performance Analysis (IPA). Furthermore, in the end it can be known that services must be repaired, and services that are in accordance with the needs of its users. Data collection techniques in this study used a questionnaire which set 100 respondents. The results of the quality analysis of the Bung Karno UPT Library Library Website have a degree of conformity of 76%, which means that the quality of services provided is not satisfactory. While the gap value (GAP) is -0.81, which means that the quality of website performance still does not meet user expectations. Then the results of the IPA Quadrant analysis are recommended to need improvements that are focused on the first quadrant and third quadrant, then based on the 3 dimensions that exist in Webqual 4.0, among others, from usability dimensions related to the improvement of information content and Website appearance. Secondly, the dimensions of information quality need to be corrected for the accuracy of information, and detailed information. Third, from the dimension of interaction, improvements need to be made to the personalization space, ease of interaction with the Institute, and promised services.